Desain Aplikasi Business To Consumer untuk UKM Berbasis Cloud Computing - Imam Asrowardi; Eko Subyantoro (Politeknik Negeri Lampung, 2015)
The importance of the role of Small and Medium Enterprises for Indonesia's economic growth give rise to the need of a business to consumer applications design that can run on cloud-based information technology infrastructure. The purpose of this research is to create an application design of business to consumer (b2c) of the SMEs to market their products which can be run on the Infrastructure as a Service (IAAS) cloud-based computing. The method used in this study is a system development life cycle (SDLC).Keywords: cloud, business, SME, SDLC